2011
DOI: 10.12693/aphyspola.120.1026
|View full text |Cite
|
Sign up to set email alerts
|

Vickers and Knoop Indentation Microhardness Study of β-SiAlON Ceramic

Abstract: In this paper, analysis and interpretation of mechanical property measurements of β-SiAlON ceramic were reported. Indentation microhardness of β-SiAlON ceramic was measured using the Knoop and Vickers indenters. The analysis of the Vickers indentation microhardness data reveals the reverse indentation size effect that is the apparent microhardness increases with increasing applied indentation test load. However, the Knoop indentation microhardness data exhibit indentation size effect that is the apparent micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 40 publications
3
19
0
1
Order By: Relevance
“…In this study, the n values vary from 1.698 to 1.735 depending on Pd additive. The decrease of H V for n < 2 as the indentation test load increases is in good agreement with other reported results [1,10].…”
Section: B-147supporting
confidence: 93%
See 2 more Smart Citations
“…In this study, the n values vary from 1.698 to 1.735 depending on Pd additive. The decrease of H V for n < 2 as the indentation test load increases is in good agreement with other reported results [1,10].…”
Section: B-147supporting
confidence: 93%
“…The curves in the graph show a non-linear behaviour of the microhardness up to certain value of applied test load after which its value tends to achieve saturation. This behaviour is called indentation size effect (ISE) [1,[10][11][12].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that the Knoop hardness H K = 14.229 (10) where P is the applied test load in N, L is the long indentation diagonal lengths in m, and 14.229 is the geometrical constant of the diamond pyramid [58]. Again it is reported that w is the width of the indentation then…”
Section: Experimental Validationmentioning
confidence: 99%
“…If the nanohardness values decrease with the increase of applied indentation test load, such phenomenon is known as indentation size effect (ISE) [7,9,10]. On the other hand, the reverse indentation size effect (RISE) means * corresponding author; e-mail: sduosman@gmail.com that micro/nanohardness value increases with increasing applied indentation load [8,11]. ISE or RISE behavior of materials show where, when, and to what extent the materials can be used.…”
Section: Introductionmentioning
confidence: 99%